2018
DOI: 10.1186/s13054-018-2260-1
|View full text |Cite
|
Sign up to set email alerts
|

Performance comparison of ventricular and arterial dP/dtmax for assessing left ventricular systolic function during different experimental loading and contractile conditions

Abstract: BackgroundMaximal left ventricular (LV) pressure rise (LV dP/dtmax), a classical marker of LV systolic function, requires LV catheterization, thus surrogate arterial pressure waveform measures have been proposed. We compared LV and arterial (femoral and radial) dP/dtmax to the slope of the LV end-systolic pressure-volume relationship (Ees), a load-independent measure of LV contractility, to determine the interactions between dP/dtmax and Ees as loading and LV contractility varied.MethodsWe measured LV pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 37 publications
3
63
0
1
Order By: Relevance
“…However, it is unclear what level of VAC, its duration, or level of exogenous catecholamines are necessary to create this detrimental effect. Recently, animal studies demonstrate that NE can impair LV ejection by increasing the magnitude of arterial pressure reflected waves during ejection, which also becomes manifest as VAC uncoupling without increasing coronary perfusion pressure [23]. As was also seen in patients with postoperative vasoplegia [11], we observed that only patients with higher Ees and normalized VAC increased CO during NE (Fig.…”
Section: Discussionsupporting
confidence: 78%
“…However, it is unclear what level of VAC, its duration, or level of exogenous catecholamines are necessary to create this detrimental effect. Recently, animal studies demonstrate that NE can impair LV ejection by increasing the magnitude of arterial pressure reflected waves during ejection, which also becomes manifest as VAC uncoupling without increasing coronary perfusion pressure [23]. As was also seen in patients with postoperative vasoplegia [11], we observed that only patients with higher Ees and normalized VAC increased CO during NE (Fig.…”
Section: Discussionsupporting
confidence: 78%
“…Blood pressure recordings were analyzed for systolic blood pressure (SBP) and the maximum rate of systolic pressure increase (dP/dt max ) as a measure of myocardial contractility. Measurement of dP/dt max from the femoral artery has been shown to provide good tracking of left ventricular contractility (Monge Garcia et al, 2018). To establish evenly sampled series, any beats for which ARI, SBP or dP/dt max measurements could not be determined were replaced by linear interpolation between the surrounding beats.…”
Section: Discussionmentioning
confidence: 99%
“…Animals were initially resuscitated with colloids (Voluven R , 130/0.4, Fresenius Kabi Deutschland GmbH, Bad Homburg, Germany) until no further increase in CO. Then they were allowed to stabilize for at least 10 min. Stability was defined as heart rate and MAP variation <5% (Monge Garcia et al, 2018). The study protocol consisted of three consecutive stages with two opposite interventions: changes in afterload (phenylephrine and nitroprusside), preload (bleeding and fluid bolus), and contractility (esmolol and dobutamine).…”
Section: Experimental Protocolmentioning
confidence: 99%